D. Mendeleiev`s collective experiments as precursors of the forms of branch research work - Kovalenko, S. D. (History of science and technology, 2017)
Two-year collective experiments performed under the supervision of D. Mendeleiev on four fields in 1867–1869 years were considered on the basis of historical and scientific analysis. It was found that carried out in different soil-climatic zones according to developed plan and methodology. Importance of the results and its implications for the future way of introduction of fertilizers in agriculture was proven.